Insomnia Severity, Subjective Sleep Quality, and Risk for Obstructive Sleep Apnea in Veterans With Gulf War Illness. Issue 9 (1st September 2016) - Chao, Linda L.; Abadjian, Linda R.; Esparza, Iva L.; Reeb, Rosemary
ABSTRACT: Despite the fact that sleep disturbances are common in veterans with Gulf War Illness (GWI), there has been a paucity of published sleep studies in this veteran population to date. Therefore, the present study examined subjective sleep quality (assessed with the Pittsburgh Sleep Quality Index), insomnia severity (assessed with the Insomnia Severity Index), and risk for obstructive sleep apnea (assessed with the STOP questionnaire) in 98 Gulf War veterans. Veterans with GWI, defined either by the Kansas or Centers for Disease Control and Prevention criteria, had greater risk for obstructive sleep apnea (i.e., higher STOP scores) than veterans without GWI. This difference persisted even after accounting for potentially confounding demographic (e.g., age, gender) and clinical variables. Veterans with GWI, defined by either the Kansas or Centers for Disease Control and Prevention criteria, also had significantly greater insomnia severity and poorer sleep quality than veterans without GWI ( p < 0.05), even after accounting for potentially confounding variables. Furthermore, there were significant, positive correlations between insomnia severity, subjective sleep quality, and GWI symptom severity ( p ≤ 0.01). In stepwise linear regression models, insomnia severity significantly predicted GWI status over and above demographic and clinical variables. Together these findings provide good rationale for treating sleep disturbances in the management of GWI.